The Comparison of Quality of Life in Scabies Patients Treated with 5% Permethrin Lotion and 10% Mimba Leaf Extract Lotion at Pondok Pesantren Malang - Rizka Melina Fauziyyah; Dhelya Widasmara; Khuznita Dasa Novita (Jurnal Ilmu Kedokteran Keluarga, 2022)
Background: Scabies is a contagious disease caused by Sarcoptes scabiei characterized by itching and lesions that affect quality of human life. Permethrin 5% as standard therapy for scabies has disadvantages in terms of price and side effects. Neem is a traditional plant that has a scabicide effect and could be an alternative treatment for scabies. Objective: to compare the quality of life of patients who were treated with 5% permethrin lotion and 10% neem leaf extract lotion using DLQI and Skindex-29 instruments. Methods: This study is an experimental design with a purposive sampling method. The sample was 42 male students in one of the Islamic boarding schools in Malang who were clinically diagnosed with scabies and met the research criteria. The research sample consisted of two groups: a group with 5% permethrin lotion therapy (21 students) and a group with 10% neem leaf extract lotion therapy (21 students). Data was collected with DLQI and Skindex-29 on day 0 before and day 14 after therapy. Data analysis used the Wilcoxon test and dependent t-test for comparison before and after therapy and independent t-test for comparison of quality of life between two therapies by using SPSS 25. Results: Statistic test to differentiate the two therapies showed p=0.670 (DLQI) and p=0.391 (Skindex-29). So, the two therapies did not differ significantly in reducing DLQI and Skindex-29 scores. Conclusion: 5% permethrin lotion and 10% neem leaf extract lotion are equally good in improving the quality of life of scabies patients. Abstrak Latar Belakang: Skabies adalah penyakit kulit menular yang disebabkan Sarcoptes scabiei dengan gejala gatal dan lesi yang berdampak pada kualitas hidup manusia. Permetrin 5% sebagai standar pengobatan skabies memiliki kekurangan dalam segi harga dan efek samping. Tanaman mimba adalah tanaman tradisional yang diduga bisa menjadi alternatif pengobatan untuk skabies karena memiliki efek skabisida. Tujuan: membandingkan kualitas hidup pasien skabies yang diterapi losion permetrin 5% dan losion ekstrak daun mimba 10% menggunakan instrumen Dermatology Life Quality Index (DLQI) dan Skindex-29. Metode: Penelitian ini merupakan design eksperimental dengan metode purposive sampling. Sampel penelitian adalah 42 santri laki-laki di salah satu pondok pesantren di Malang yang secara klinis terdiagnosis skabies. Sampel penelitian terdiri dari dua kelompok yaitu: satu kelompok dengan terapi losion permetrin 5% (21 santri) dan satu kelompok dengan terapi losion ekstrak daun mimba 10% (21 santri). Pengumpulan data menggunakan DLQI dan Skindex-29 pada hari 0 sebelum terapi dan hari 14 setelah terapi. Analisis data menggunakan uji Wilcoxon dan uji t-dependen untuk perbandingan sebelum dan sesudah terapi dan uji t-independen untuk perbandingan kualitas hidup antara dua terapi mengunakan SPSS 25. Hasil: Hasil uji statistik perbedaan 2 obat menunjukkan p=0,670 dengan parameter DLQI dan p=0,391 dengan parameter Skindex-29. Sehingga terapi dua losion tersebut tidak berbeda secara signifikan dalam menurunkan skor DLQI dan Skindex-29). Kesimpulan: losion permetrin 5% dan losion ekstrak daun mimba 10% sama baiknya dalam meningkatkan kualitas hidup pasien skabies. Kata Kunci: Skabies, Kualitas Hidup, Permetrin, Daun Mimba Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332706